BENTUK PETRI NET DAN MODEL ALJABAR MAX PLUS PADA SISTEM PELAYANAN PASIEN RAWAT JALAN RUMAH SAKIT AL HUDA GENTENG, BANYUWANGI - Siska Aprilia Hardiyanti; Ika Yuniawati; Aprilia Divi Yustita (Mathematics Department of Mathematics and Natural Sciences Unisda Lamongan, 2017)
The hospital is one of the service providers that can not be separated from the queue problem. Queues can occur if the number of patients who come more than the existing service facilities. The hospital services used in this study are outpatient services performed by BPJS and non BPJS patients. In addition, in this paper, a Petri net model of queuing outpatient service system system at Al Huda Genteng Banyuwangi Hospital,and max algebra model was added to estimate the length of waiting time of the patient.